2023
DOI: 10.3390/foods12142671
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnological Applications of Mushrooms under the Water-Energy-Food Nexus: Crucial Aspects and Prospects from Farm to Pharmacy

Abstract: Mushrooms have always been an important source of food, with high nutritional value and medicinal attributes. With the use of biotechnological applications, mushrooms have gained further attention as a source of healthy food and bioenergy. This review presents different biotechnological applications and explores how these can support global food, energy, and water security. It highlights mushroom’s relevance to meet the sustainable development goals of the UN. This review also discusses mushroom farming and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 156 publications
(175 reference statements)
0
3
0
Order By: Relevance
“…The vitamin B1, B2, B3 and B12 contents of Pleurotus ostreatus reported in this study was higher than the values reported by Majesty et al ( 2 ) as 0.10 mg, 0.57 mg, 0.40 mg and 0.16 mg, respectively, and lower than 0.91 mg of vitamin B6. The rich vitamin B content of Pleurotus ostreatus enables it function in boosting the immune system, enhancing DNA synthesis ( 73 ) and improve red blood cells production, making it very suitable to be consumed by pregnant women, menstruating females and anaemic patients ( 74 ).…”
Section: Discussionmentioning
confidence: 99%
“…The vitamin B1, B2, B3 and B12 contents of Pleurotus ostreatus reported in this study was higher than the values reported by Majesty et al ( 2 ) as 0.10 mg, 0.57 mg, 0.40 mg and 0.16 mg, respectively, and lower than 0.91 mg of vitamin B6. The rich vitamin B content of Pleurotus ostreatus enables it function in boosting the immune system, enhancing DNA synthesis ( 73 ) and improve red blood cells production, making it very suitable to be consumed by pregnant women, menstruating females and anaemic patients ( 74 ).…”
Section: Discussionmentioning
confidence: 99%
“…This nexus has a very close relation to global climate change [131], the sustainable use of these resources [132], the sustainability of desalination [133], the ecosystem [134], and rainwater harvesting in arid zones [135]. This WEF nexus has a very closed relationship among all its components (water, energy, and food), which the factors of each component depend on each other, as well as it is impossible to secure any resource (e.g., food) without securing the others (i.e., water and energy) and vice versa [129,136].…”
Section: Nanofibers In Water-energy-food Nexusmentioning
confidence: 99%
“…In modern medicine, mushrooms are of interest as a source of many biologically active compounds, including polysaccharides, terpenoids, steroids, lectins, statins, polyphenols, phenols, alkaloids, antibiotics, etc., which may enhance immune function or have antitumor, antioxidant, antiviral, antibacterial, and other activities. Compounds such as lignocellulosic enzymes, lectins, proteases, and protease inhibitors have been used for the development of new drugs [45,46]. Investigation of the biotechnological potential of the LE-BIN collection strains will be covered below in the relevant sections.…”
Section: Ex Situ Conservation Of Macromycetes Diversitymentioning
confidence: 99%